2017
DOI: 10.1177/0306624x17723626
|View full text |Cite
|
Sign up to set email alerts
|

Many Shades of Green: Assessing Awareness of Differences in Mental Health Care Needs Among Subpopulations of Military Veterans

Abstract: The current study sought to examine access to services by various veteran subgroups: racial/ethnic minorities, females, rural populations, and LGBTQ (Lesbian, Gay, Bisexual, Transgender, and Queer). Generally, the Veteran Service Officers (VSOs) interviewed for this study did not feel that these subgroups were well served by the program and treatment options presently available, and that other groups such as males and urban veterans received better access to necessary psychosocial and medical care. This resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…However desirable it is, social support may be difficult to attain in the context of challenges to work-life balance [ 42 ]. Lastly, the three women call attention to inconsistency in gender sensitivity in VA health services [ 22 , 26 ]. Furthermore, these cases illustrate barriers to access care and pressure for self-advocacy in response to feeling undervalued or dismissed by VA health practitioners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However desirable it is, social support may be difficult to attain in the context of challenges to work-life balance [ 42 ]. Lastly, the three women call attention to inconsistency in gender sensitivity in VA health services [ 22 , 26 ]. Furthermore, these cases illustrate barriers to access care and pressure for self-advocacy in response to feeling undervalued or dismissed by VA health practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…The social needs of transitioning women veterans intersect with their experience in the military, as well as existing economic and social norms, such as prevailing family or gender roles [ 20 , 21 ]. Recent research has shown that many veterans service organizations (VSOs) tend to focus on rank, branch, or other military characteristics to distinguish between veterans rather than issues of race, sexuality, or gender, [ 22 ] and that women do not typically feel welcomed at traditional VSOs [ 23 ]. Studies have also demonstrated that “universalist” health programs are, in practice, oriented toward men and lack gender sensitivity, which tends to marginalize women veterans in clinical treatment and discourage continuity in care [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not possible to generalize results to various veteran demographics (e.g., age, branch of service, rank, and combat experience). The present focus could contribute to sample bias as the veteran population is becoming more diverse and barriers to services exist for veteran subgroups (see Ahlin & Douds, 2018). It is possible that different themes may emerge among other samples.…”
Section: Limitations and Future Researchmentioning
confidence: 98%
“… 22–24 There is also evidence suggesting that gender, age, and rank may play a role. For example, some research has shown that women 25 26 and sexual minority 27 military personnel were less likely to access care, while other research has shown that men, older individuals, those in service support occupations (ie, logistics technicians and cooks relative to other trades), those of higher ranks, and those with fewer years of service were less likely to access care. 9 28 The associations between organisational factors and barriers to seeking mental healthcare have been less studied.…”
Section: Introductionmentioning
confidence: 99%